Strategic Management, 3e - Morris,John; Tripathi,Sanjai (2022)
This book is being updated under a grant from the OERU of Oregon State. This open source textbook is derived from many sources, initially (1st edition) from the Principles of Management by Carpenter, Bauer, and Erdogan, but there is abundant new content as well. It is published under a Creative Commons license and as such there is no charge ever for this textbook. In addition to taking on a second author, the most important change from 2e is that three tenured faculty have signed on to consider, review, and approve the content. This edition will have a more global perspective and make a tighter linkage with the Micromatic simulation software as well as provide mini-case studies for classroom discussions.
Keywords: Management; Strategy & Entrepreneurship